2004
DOI: 10.1007/s00374-004-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of earthworms (Eisenia fetida) in influencing bioavailability of heavy metals in soils

Abstract: The effects of earthworm (Eisenia fetida) activity on soil pH, dissolved organic carbon (DOC), microbial populations, fraction distribution and bioavailability of heavy metals (Zn, Cu, Cr, Cd, Co, Ni, and Pb) in five Chinese soils were investigated using pot experiments. A three-step extraction procedure recommended by the European Community Bureau of Reference (BCR; now Standards, Measurements and Testing Programme of the European Community) was used to fractionate the metals in soils into water soluble, exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(50 citation statements)
references
References 31 publications
3
44
3
Order By: Relevance
“…The significant difference was observed for the C 2 concentration, which represents the highest CaCl 2 extractable Cd soil concentration. These findings are inconsistent with previous studies, which suggested an increase in the availability of metal fractions as a result of earthworm activities (Wen et al, 2004;Coeurdassier et al, 2007;Udovic and Lesta, 2007). Lukkari et al (2006) however reported an increase of Zn fractions in the presence of earthworms, concluding that earthworms tended to decrease the mobility of Zn in the soil.…”
Section: Effects Of Earthworms and Plants On The Ph And The Availabilcontrasting
confidence: 98%
See 2 more Smart Citations
“…The significant difference was observed for the C 2 concentration, which represents the highest CaCl 2 extractable Cd soil concentration. These findings are inconsistent with previous studies, which suggested an increase in the availability of metal fractions as a result of earthworm activities (Wen et al, 2004;Coeurdassier et al, 2007;Udovic and Lesta, 2007). Lukkari et al (2006) however reported an increase of Zn fractions in the presence of earthworms, concluding that earthworms tended to decrease the mobility of Zn in the soil.…”
Section: Effects Of Earthworms and Plants On The Ph And The Availabilcontrasting
confidence: 98%
“…The presence of earthworm increased Cd concentration in Z. mays, except for the control, probably because the amount of available Cd was too low. An increase in metal concentration for plants in the presence of earthworms was also observed by Wen et al (2004). Yu et al (2005) found that earthworm activities increased Cd uptake and plant growth, thereby improving the phytoextraction efficiency of metal hyperaccumulators in low to medium level metal-contaminated soils.…”
Section: Earthworm and Plants Interactionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, a novel test, namely, simulated earthworm gut, recently developed based on the enzymatic composition of the gastrointestinal fluid of E. andrei appeared to be most promising for predicting availability of metals in soil than chemical extraction methods [44]. The concentration of bioaccessible Bi recorded in the present study due to E. andrei activity was greater than those reported by Wen, et al [45] for Cr, Co, Ni, Zn, Cu, Cd, and Pb using E. fetida. This was possibly caused by a stronger affinity of Bi to form chelating complexes with metallophores and other biomolecule produced by earthworm.…”
Section: Total and Bioaccessible Bi In Soilcontrasting
confidence: 50%
“…To prevent the substrate from escaping through the holes at the bottom and the possibility of roots growing out of the pots (Hu et al 2013a, b), pieces of frost cloth were placed at the bottom before placing the substrate. Since the 100 % water-holding capacity (WHC) of tailings was determined prior to trial set-up, each pot containing the mixed substrate was adjust to 60 % WHC using tap water and left to stabilize for 2 days (Ruiz et al 2009;Wen et al 2004;Wang et al 2007). Thereafter, 25 seeds (Grant et al 2002) of Cynodon dactylon were sown 2 cm deep (Du et al 2014) in each pot.…”
Section: Methodsmentioning
confidence: 99%